2012
DOI: 10.1177/0264550511429842
|View full text |Cite
|
Sign up to set email alerts
|

Identifying personality disturbance in a London probation sample

Abstract: Personality difficulties provide challenges to offender management, particularly in regard to risk and diagnosis. No provisions exist for identifying personality disturbance in probation services, despite a political emphasis on the need for specialist knowledge of this group in the criminal justice system. This article reports on a pilot project where mental health professionals collaborated with probation services to develop methods of identifying personality disturbance in a London sample. There was a dispr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…The results of this study refer to a proportion of the sample that received more intensive input ( N = 341, 46%). Offenders were included if they reached a threshold on a screen for PD (Minoudis et al, ) and if there were additional problems, including offending behaviour programmes not being sufficient to address identified needs, being at an impasse in sentence progression, having adjudications for violence in prison and not meeting sentence plan objectives.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study refer to a proportion of the sample that received more intensive input ( N = 341, 46%). Offenders were included if they reached a threshold on a screen for PD (Minoudis et al, ) and if there were additional problems, including offending behaviour programmes not being sufficient to address identified needs, being at an impasse in sentence progression, having adjudications for violence in prison and not meeting sentence plan objectives.…”
Section: Methodsmentioning
confidence: 99%
“…Table shows the total number of cases screened into the pathway at June 2016 was 36,459, 37% of the total NPS cases. ‘Screening in’ means that these cases have been rated positive for more than seven of the OASys variables indicating personality disorder and/or one of four other factors (childhood difficulties, mental health problems, current behavioural difficulties and history of self‐harm or suicide attempts) that may indicate personality disorder (Craissati and Sindall, ; Minoudis et al, ; Shaw et al, ), coupled with the standard assessment of risk.…”
Section: Descriptive Analysis Of Cases Screened In To the Offender Pementioning
confidence: 99%
“…Evaluations of the core community service have shown that offender managers value their training in managing complex behaviour, rates of recall are reduced and compliance of offenders can be increased. In addition, research has shown that better understanding of offenders through psychological formulation has led to offenders accessing services where previously they were at an impasse (Brown et al, ; Bruce et al, ; Clark and Chuan, ; Minoudis et al, 2012a, 2012b, 2013). These studies are small, do not have robust control groups and ultimately do not measure the two main outcomes of reduced reoffending and improved psychological well‐being.…”
Section: Evaluating the Pathwaymentioning
confidence: 99%
“…In order to screen all those on London probation caseload when the pathway was introduced and prospectively screen those being referred at sentence, an algorithm was developed, which facilitated automated screening of certain elements (see Minoudis et al, ). This included an assessment of both risk and personality disorder.…”
Section: Overview Of Pathwaymentioning
confidence: 99%